Preparing Future Handicraft Teachers for Inclusive Education in Ukrainian Schools - Androshchuk, Iryna; Androshchuk, Ihor; Krasylnykova, Hanna (Journal of Vasyl Stefanyk Precarpathian National University, 2021)
The paper highlights the results of empirical research regarding the issues undermining the implementation of inclusive education in the context of training handicraft teachers and, consequently, discovers effective ways to eliminate them. It shows that future handicraft teachers are mostly not ready to implement inclusive education. This is due to the lack of adequate knowledge and skills required to work with children with special needs. Besides, the paper indicates students’ unawareness of categories of children with special needs and characteristics of correctional and developmental work in handicraft lessons, including relevant exercises, motor activity. This fact negatively affects future teachers’ emotional readiness to work under such conditions. Working with various tools while processing structural materials requires adherence to safety rules in lessons and appropriate organization of design and technological activities. The paper specifies that teacher placement supervisors do not have the necessary experience of working with children with special needs and thus cannot prepare their students for that. Also, it justifies the need to develop students’ emotional readiness to work with children with special needs, update the content of professional training for future handicraft teachers, taking into account the specifics of inclusive education, develop their ability to employ teaching methods appropriate for inclusive classes in handicraft lessons. Finally, the paper isolates the main areas that can help to increase the effectiveness of professional training of future handicraft teachers in higher education institutions so that they can work with children with special needs.